İbretnüma (2009) in the context of shadow play representation language with a feminist approach - Berceste Gülçin Özdemir; Nilay Ulusoy (ARTS: Artuklu Sanat ve Beşeri Bilimler Dergisi)

(untitled)
Istanbul-born visual artist and activist Canan Şenol, also known as Canan (1970-), produced the video animation İbretnüma (2009), which tells the story of a young girl who moves from an Anatolian village to a big city. Using a contemporary art approach, the work incorporates representations that influence traditional Turkish art. The video animation features a diverse range of visuals, including traditional Turkish shadow play, largely derived from original artifacts and combined with collage elements, to represent the female body in all its aspects. By subverting patriarchal ideologies and the non-verbal restrictions imposed on women during Turkey’s modernization process, the work synthesizes avant-garde and feminist approaches in its representation techniques, blending traditional and contemporary art forms. This allows for an examination of the female character’s position in both public and private spheres, informed by feminist film theory and the concepts explored in the work.